High torque and excessive vibration on the induction motors under special voltage fluctuation conditions. Issue 4 (19th August 2021) - Ghaseminezhad, Morteza; Doroudi, Aref; Hosseinian, Seyed Hossein; Jalilian, Alireza
Abstract : Purpose: Voltage fluctuation (flicker) is a power quality disturbance that can produce several undesirable effects on industrial equipment. This paper aims to present the methodology and results of investigations undertaken to examine the speed and torque of an induction motor (IM) under voltage fluctuation conditions. Design/methodology/approach: The IM response to different characteristics of voltage fluctuations is presented. It will be shown that under a special condition the IM torque can even reach two times the rated torque. To show how this occurs, a qualitative discussion is given on the motor response by linearized equations. Findings: The small-signal analysis was used to determine the frequency which leads to maximum speed fluctuations. It was shown that, if the motor is excited with a modulation frequency (resonant frequency) which is one of its natural frequencies (modes), the mode will act as a fluctuating amplifier and greatly increase the amplitude of torque and speed fluctuations. Sensitivity analysis is also carried out to evaluate the influence of motor parameters on the resonance frequency. The results show that the resonance frequency is not affected at all by the changes in magnetizing reactance. This has been shown that magnetic saturation does not have any impact on the resonance frequency. The most effective parameters are rotor and stator resistances. Originality/value: With the increasing popularity and use of arc furnace loads in the metallurgy industry and due to the wide application of large IMs in the industry, it is possible that the frequency of torque pulsation locates near a natural frequency and then will create an oscillation with a large magnitude, potentially leading to accelerated fatigue or severe damage of shaft. However, if this phenomenon occurs in industries, the resonance frequency must be filtered from the input voltage. Experimental results on a 1.1 kW, 380 V, 50 Hz, 2 pole IM are used to validate the accuracy of simulation results.